Implementation Of Gender Equality In The Leadership Of The Pergerakan Mahasiswa Islam Indonesia Organization - Iwah Pakungwati; Tri Suminar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to look at the implementation of gender equality in PMII Komisariat Al-Ghozali Semarang by using four main indicators: access, participation, control, and benefits. In addition, this study also explores the supporting and inhibiting factors that influence the realization of gender-equitable leadership. This research uses descriptive qualitative method with participatory observation, in-depth interviews, and documentation as data collection techniques. The informants consisted of the chairperson, secretary, head of the internal division, and two general members. The findings show that women administrators have gained relatively equal access and opportunities to participate. However, they are still underrepresented in aspects of control and strategic decision-making, which are still largely dominated by male colleagues. Supporting factors include early exposure to gender awareness through formal regeneration programs such as the New Member Admission Period and the Gender Islamic School. Meanwhile, inhibiting factors mainly consist of low self-confidence among female cadres and male dominance in key organizational roles. This research offers a new perspective by discussing gender equality in the context of faith-based student organizations-an area that remains largely unexplored. The findings of this study contribute to efforts to shape internal organizational policies that are more inclusive, participatory, and responsive to gender justice.